CULTURAL CONSCIOUSNESS AND DINKAR’S VISION IN INDIAN LITERATURE - Kumar, Priyanshu (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Indian literature is known for its cultural diversity and deep philosophical traditions. This literature is not only a mirror of the society, but it is also a carrier of cultural consciousness. Ramdhari Singh ’Dinkar’ worked to highlight and give direction to the cultural consciousness of Indian society in his literature. In his literature, there is a deep sense of harmony between tradition and modernity, religious tolerance, and nationalism. This research paper analyzes Dinkar’s literary vision and attempts to show how his literature was helpful in the development of Indian cultural consciousness.